Operating outside the spirit of the law: How police employ “legal” standards to justify questionable searches and seizures - Nir, Esther (International journal of police science & management, 2022)
The Fourth Amendment protects individuals against unreasonable searches and seizures. Over the years, court precedents have guided determinations of reasonableness and provided a legal structure for police to follow. In two influential decisions, the Supreme Court validated pretextual traffic stops in which the motorist committed a minor traffic violation (Whren v United States, 1996), and established the standard of reasonable suspicion for brief investigatory stops and limited weapon searches (Terry v Ohio, 1968). Using 42 suppression motions filed in a US state, we examine whether and how police apply these legal parameters to case patterns to justify stops, searches and seizures. We find that police use pretexts to justify traffic stops, and often rely on conclusory and laconic descriptions to support determinations of reasonable suspicion. Although often upheld by courts, these applications of the law are contrary to the spirit of the Fourth Amendment.